PHYSIOTHERAPY MANAGEMENT FOR LUMBAL STRETCHING EXERCISE AND LUMBAL CORE STABILIZATION EXERCISE IN CHRONIC LOW BACK PAIN: A CASE STUDY - Putri, Yulinda Permata; Naufal, Adnan Faris; Wijayaningsih, Anteng (Academic Physiotherapy Conference Proceeding, 2021)
Introduction: Chronic low back pain refers to the low back, lumbosacral and sacroilliac pain over 3 months which is sometimes accompanied by radiating pain in the lower extremities. LBP is one of the most common musculoskeletal disorders with a prevalence rate of 80%. LBP treatment can be done with medication and physiotherapy programs.The purpose of this study was to determine the effectiveness of a physiotherapy program using MWD, Tens, stretching exercise and lumbal core stabilization exercise to reduce pain, improving range of motion and optimizing functional ability in patient with CLBP. CasePresentation: Mr. Y feels pain in the lower back, left buttocks and left hamstring since 1 year ago, sometimes he feels tingling and cramping in his left leg. The patient also complained of pain in the left hip area and was known to have a history of falling from his motorcycle and cracking his left hip. The patient is unable to walk long distances, feels pain in the waist if he sits too long, feels pain when bending his back and unable to lift heavy weights from the floor. The complaints will be reduced when used to rest. Management and Outcome: The patient attended therapy three times once a week with a physiotherapy programs MWD, Tens, Stretching Exercise and Lumbal Core Stabilization Exercise. Patient were evaluated using Numerical Rating Scale (NRS), Meterline, Goneometer, Manual Muscle Testing (MMT), and Oswestry Disability Index (ODI). Conclusion: Physiotherapy program for 1 months with the intensity of patient visits once a week with the intervention of MWD, Tens, Stretching Exercise and Lumbar Core Stabilization Exercise can reduce pain intensity, increasing left hip range of motion and increase the patient's functional ability.